2011
DOI: 10.1007/s00264-011-1268-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of navigation assisted cup placement in total hip arthroplasty

Abstract: Purpose Computer navigation has the potential to provide precise intraoperative knowledge to the surgeon. Previous studies with navigation have confirmed its function for improved component position but few studies have reported the accuracy and precision of navigation system in clinical use. With this study we propose to evaluate the efficacy of navigation in guiding cup placement. Methods Fifty-six patients undergoing primary total hip arthroplasty were prospectively included in this study. Stryker imageless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…On the other hand, Bosker et al [18] showed that the 70.5 % of cups in primary THA were positioned within the safe zone by a freehand technique. In recent studies, improved cup position using computer navigation [21,22] and its accuracy [23] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bosker et al [18] showed that the 70.5 % of cups in primary THA were positioned within the safe zone by a freehand technique. In recent studies, improved cup position using computer navigation [21,22] and its accuracy [23] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted surgery (CAS) has been shown to improve the accuracy and reproducibility of component position compared to manual techniques [7,9,11,20,[22][23][24]. Many CAS systems for THA reference the anterior pelvic plane (APP), a spatial plane defined by bilateral anterior-superior iliac spines (ASIS) and the pubic tubercle, to determine acetabular component anteversion [29].…”
Section: Introductionmentioning
confidence: 99%
“…While the standing position and the adjustment for pelvic tilt in acetabular parameter measurement are not routinely used in clinical practice, they allow the evaluation of acetabular anatomy without the bias induced by positioning. These parameters would also remain accurate in an operative setting since the surgeon could either use a navigation system (similar to the one used in total hip arthroplasty placement) (Babisch et al, 2008;Kumar et al, 2012) or position the patient such as it is at 0°o f tilt (APPA = 0°) in order to remain concordant with the measurements performed by this system. Acetabular anteversion was found to be significantly smaller in subjects with DS, which is in accordance with previous studies on this patient population (Abousamra et al, 2016;Sankar et al, 2011;Sankar et al, 2012;Woolf and Gross, 2003).…”
Section: Discussionmentioning
confidence: 99%